2017
DOI: 10.1080/15476286.2017.1377879
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution of the translational machinery optimizes initiation with unusual initiator tRNAs and initiation codons in mycoplasmas

Abstract: Initiator tRNAs (i-tRNAs) are characterized by the presence of three consecutive GC base pairs (GC/GC/GC) in their anticodon stems in all domains of life. However, many mycoplasmas possess unconventional i-tRNAs wherein the highly conserved sequence of GC/GC/GC is represented by AU/GC/GC, GC/GC/GU or AU/GC/GU. These mycoplasmas also tend to preferentially utilize non-AUG initiation codons. To investigate if initiation with the unconventional i-tRNAs and non-AUG codons in mycoplasmas correlated with the changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…7c). The present observations in the archaeal system agree with previous studies in E. coli showing that the central GC pair and particularly base G30 was the most crucial nucleotide for translation fidelity [64][65][66] .…”
Section: Discussionsupporting
confidence: 93%
“…7c). The present observations in the archaeal system agree with previous studies in E. coli showing that the central GC pair and particularly base G30 was the most crucial nucleotide for translation fidelity [64][65][66] .…”
Section: Discussionsupporting
confidence: 93%
“…The uS12 and IF3 do not directly interact with each other in SSU (Figure 2a) (Hussain et al., 2016). However, our earlier studies suggested the possibility of coevolution of variations in uS9, IF3 and uS12 proteins of the translation machinery in mycoplasma species harboring variations in the 3GC region of the i‐tRNA (Figure ) (Ayyub et al., 2018a).…”
Section: Resultsmentioning
confidence: 99%
“…To advance our understanding of the significance of the infC V93A mutation in the suppressors, we utilized a well characterized infC135 allele of IF3 bearing the mutation Arg131Pro, which is known to, (a) confer errors in start codon discrimination, (b) allow initiation with non‐3GC bp containing i‐tRNAs, (c) possess altered binding efficiency to the ribosomes, and (d) exhibit a loss of autoregulation of IF3 from its AUU start codon (Haggerty & Lovett, 1993, 1997; O’Connor et al., 2001). Interestingly, the Arg131Pro variation is naturally found in IF3 in mycoplasma possessing the au/GC/Gu variant i‐tRNA and has been shown to play an important role in accommodation of the variant i‐tRNA in the ribosome (Ayyub et al., 2018a). We transduced DK‐GC/GC/GC, DK‐cg/GC/cg, Sup‐1 and Sup‐2 strains with the infC135 allele (Figure 6a(i)) and checked its effects on the growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning uS13 and uS19, the C-tails of these two proteins are oriented toward the major groove of the anticodon stem of the initiator tRNA (Figure 7). In particular, they interact with G30 of the second base pair of the almost universally conserved three GC base pairs of the anticodon stem of the initiator tRNA, that play a crucial role in translation fidelity (Samhita et al, 2012;Hussain et al, 2016;Shetty et al, 2017;Ayyub et al, 2018). Sequence alignments of uS13 showed that the basic character of the C-tail is conserved in the three domains of life.…”
Section: Three Universal Proteins Participate In the Selection Of Thementioning
confidence: 99%